Changes in agrochemical parameters of leached chernozem under the influence of differentiated use of minerals - A. A. Artemjev; A. M. Guryanov (Аграрная наука Евро-Северо-Востока)
The article presents the results of studies conducted in 2004-2010 at the experimental plot in the forest-steppe Volga region. The research investigated the impact of traditional (average) and differentiated use of mineral fertilizers in the field crop rotation (winter wheat (reconnaissance sowing) – spring wheat ‒ annual grass – spring barley – bare fallow– winter wheat – spring wheat) on the change of agrochemical properties of leached chernozem. It was established that the six-year use of fertilizers contributed to the improvement of the main indicators of top soil fertility regardless of application technology. On average, in 15 sectors (plots) of each variant, the content of mobile phosphorus per rotation of crop rotation increased with differentiated fertilization by 15.9%, potassium – by 15%, and in the traditional one – by 4.8 and 16.7% respectively, (control of 100.8 and 116.2 mg/kg of soil, respectively). In sectors where no fertilizer was applied, the content of mobile elements decreased by 2-7%. The nitrogen content in the soil directly depended on the timing of sampling and the amount of moisture in the soil, so it was difficult to track its change. The difference in the accumulation of mineral nitrogen between the technologies of fertilizer application was not observed. For organic matter in all variants of the experience over the years of research there was a decrease in the indicator. This was more noticeable in the control, where the value decreased by 2.7%. Here, the value of soil acidity increased by 0.12 units and became 4.7. In variants with fertilizers soil acidity remained the same (4.6-4.7). In general, the differentiated use of mineral fertilizers did not have a negative influence on the agrochemical composition of leached chernozem. There was a gradual equalization of soil fertility due to the residual amounts of phosphorus and potassium on low-fertile plots and some reduction of mobile elements in zones with high content.